2018
DOI: 10.1093/mnras/sty1166
|View full text |Cite
|
Sign up to set email alerts
|

Dusty disc–planet interaction with dust-free simulations

Abstract: Protoplanets may be born into dust-rich environments if planetesimals formed through streaming or gravitational instabilities, or if the protoplanetary disc is undergoing mass loss due to disc winds or photoevaporation. Motivated by this possibility, we explore the interaction between low mass planets and dusty protoplanetary discs with focus on disc-planet torques. We implement Lin & Youdin's newly developed, purely hydrodynamic model of dusty gas into the Pluto code to simulate dusty protoplanetary discs wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 90 publications
(110 reference statements)
2
24
0
Order By: Relevance
“…Compared to the simulation with St = 0.1, the Time=400 panel of the pebble surface density reveals that only a few vortices are formed at the planet separatrix, but with a larger radial size. Extrapolating down to smaller values of the Stokes number, we would expect that a large, single vortex to be eventually formed in the limit of small dust grains with St → 0, which would be consistent with the results of Chen & Lin (2018). From the pebble surface density profile that is plotted for each model in the left panel of Fig.9, it appears that this arises because the width of the separatrix tends to increase as the Stokes number decreases, resulting in a weaker bump in the generalized PV profile (see right panel of Fig.…”
Section: Evolution As a Function Of Stokes Numbersupporting
confidence: 83%
See 1 more Smart Citation
“…Compared to the simulation with St = 0.1, the Time=400 panel of the pebble surface density reveals that only a few vortices are formed at the planet separatrix, but with a larger radial size. Extrapolating down to smaller values of the Stokes number, we would expect that a large, single vortex to be eventually formed in the limit of small dust grains with St → 0, which would be consistent with the results of Chen & Lin (2018). From the pebble surface density profile that is plotted for each model in the left panel of Fig.9, it appears that this arises because the width of the separatrix tends to increase as the Stokes number decreases, resulting in a weaker bump in the generalized PV profile (see right panel of Fig.…”
Section: Evolution As a Function Of Stokes Numbersupporting
confidence: 83%
“…12. This is due to the fact that gradients at the separatrix are better resolved (Chen & Lin 2018), as can be observed in the lower right panel of Fig. 12 which displays the profiles of the generalized PV function at Time=50 and for both resolutions.…”
Section: Effect Of Resolutionmentioning
confidence: 71%
“…Dust can also concentrate due to torques exerted by low-mass planets (e.g. Chen & Lin 2018). It has also been shown that dust can concentrate because of vortices induced by the self-organization due to the Hall effect in magnetized disks (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Hutchison et al (2018) improved this method and adapted it to treat simultaneously several dust species. Lin & Youdin (2017) and Chen & Lin (2018) have applied the monofluid formalism on a cylindrical grid adapted to protoplanetary disk simulations with an Eulerian approach.…”
Section: Introductionmentioning
confidence: 99%